(untitled) (Journal of actual problems of jurisprudence, 2018)
The article analyzes the level of legal regulation of corrective punishment in the renewed criminal legislation of the Republic of Kazakhstan. In punitive content of correctional labor, the central focus has been shifted to proprietary restrictions, and compulsory work faded into insignificance, which, in the author’s opinion, increases the similarity of correctional works with the penalty. As the result of this, he names correctional works as “penalty by installments”, characterizes its role in the system of punishments as proprietary punishment related to the labor impact. The scientist rationalizes that the correctional labor is stricter punishment than the penalty by the nature of legal restrictions, as the right for receiving of remuneration for the labor, right for the labor freedom, right for the free selection of the activities type and profession of the person convicted for the correctional labor is restricted. For the purpose of improvement of the legal regulation of the correctional labor, the article’s author proposes the ways for determination of the basic employment place of the person convicted of this type of punishment, criteria which are to be made allowance for in determination of the general amount of deductions and interests of monthly payments to the state revenue from the convict’s earnings (financial allowance). In order to eliminate the significant disadvantage in the legal regulation of the correctional labor stipulated in the list of juvenile punishments, he proposes to set the correctional labor rate to the influence of the fact that they are restricted whether for the crime or criminal infraction. Key words: punishment, a system of punishments, basic punishments, correctional labor, penalty, proprietary punishments, punishments related to correctional impact, compulsory work, basic employment place, punishment rate.